THE USE OF CODE-SWITCHING AMONG THE LATE ADOLESCENTS IN SOCIAL MEDIA FACEBOOK - Lubis, Indah Sari; Surya, Satyawati; Muka, Adinda Usin (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2017)
This study discussed the use of code-switching among the late adolescents in social media Facebook. The purpose of the research was to know the types of code-switching used among the late adolescents in social media Facebook by applying Poplack theory. The other purpose was to reveal the reasons for using such types of code-switching in social media Facebook by applying Hoffman theory. The descriptive qualitative research design was used in this study. The data of the research were analyzed using Miles and Huberman method. The results of the research were: (1) there were three types of code-switching used by the late adolescents in social media Facebook, (2) some reasons in using code-switching were being emphatic to others, the use of interjection to gain attention, the use of repetition for clarification, intention of clarifying the speech content for interlocutor, expressing identity group, softening the request or command, lexical needs, and using  satire. Satire was mostly found in this research.Keywords: code-switching, late adolescent, social media